Anti-inflammatory effects of Cordyceps mycelium (Paecilomyces hepiali, CBG-CS-2) in Raw264.7 murine macrophages - Park, Seong-Yeol (Orient Pharm Exp Med, 2014)
Cordyceps (CS) is a traditional Chinese herb with various biological effects that include immune modulation. CBG-CS-2 is a strain, Paecilomyces hepiali, of the Cordyceps spp. The anti-inflammatory effects of CBG-CS-2 were investigated. The water-soluble fraction of CBG-CS-2 has high anti-inflammatory activity in LPS-induced Raw264.7 macrophages. We tested the role of CBG-CS-2 on the anti-inflammation cascade in LPS-stimulated Raw264.7 cells. CBG-CS-2 significantly decreased NO production, iNOS expression, and pro-inflammatory cytokine secretion in a dose-dependent manner. To investigate the mechanism by which CBG-CS-2 inhibits NO, iNOS, and pro-inflammatory cytokines, we examined the activities of NF-κB and AP-1 in LPS-activated macrophages. The results demonstrate that CBG-CS-2 suppresses the production and expression of NO, iNOS, and pro-inflammatory cytokines in LPS-activated macrophages via inhibition of NF-κB and AP-1, which may play an important role in inflammation. These findings suggest that CBG-CS-2 has modulatory effects on the inflammatory system in macrophages, and that it can serve as a useful anti-inflammatory dietary supplement or drug.